Sir Percy Loraine and British Relations with Italy, 1939-1940. Issue 2 (2nd April 2020) - Richardson, Adam
ABSTRACT: One of only four men to represent Britain as ambassador in Rome during the interwar period, Sir Percy Loraine's tenure in the Italian capital lasted just over 400 days and ended with Italy's entry into the Second World War. This analysis explores three areas of Loraine's ambassadorship in Rome, showing that he was a reliable, robust, and respected representative suited to dealing with Italian Fascism. First, it examines Loraine's views towards Italy as he worked to promote cordial Anglo-Italian relations prior to the outbreak of the war and during the period of Italian non-belligerence. Second, it explores how Loraine dealt with Benito Mussolini, the Italian dictator – whom he met only twice officially – and Italian Foreign Minister Galeazzo Ciano, with whom he built a strong rapport. Finally, it considers Loraine's relationship with his Foreign Office colleagues, which was strong and demonstrates a continued agreement with and respect for the ambassador's work.